Responsabilidad civil y omisión de reconocimiento de paternidad al hijo extramatrimonial en el juzgado de familia de Maynas, 2020 - Chávez Huamán, Valentín (2024)
In the Maynas region, the failure to recognize extramarital paternity is a complex social phenomenon, aggravated by the lack of a specific legal framework that addresses its civil and social implications. This research analyzes the relationship between the failure to recognize and the civil liability of the parent in the context of the Maynas Family Court in 2020, with a focus on the dimensions of damage and fault or fraud in the behavior of the parent. This quantitative, correlational and non-experimental study uses surveys of justice operators and the analysis of judicial files, revealing a significant correlation between the variables, which suggests the need for clear and effective legislation. The results indicate that 70% of those surveyed consider it essential to incorporate specific rules that regulate civil liability in these cases. 60% maintain that the omission harms the minor's right to identity, highlighting the relevance of formal recognition to protect their rights. The statistical analysis shows a correlation coefficient of 0.863 and a p-value of 0.000, validating the proposed hypotheses. Furthermore, 70% of the participants are in favor of the minor's right to claim damages being imprescriptible, underlining the urgency of establishing a regulatory framework with adequate reparations. The conclusions highlight the need to address the legal and social implications of non-recognition, promoting the protection of the rights of the minor and the civil responsibility of the parent in family law.